The "Two-Way Street" of Having an Impact: A Democratic School's Attempt to Build a Broad Counterhegemonic Alternative. Issue 3 (March 2015) - Meshulam, Assaf
Background/Context: Critical education studies tries to make sense of the relationship between education and differential power in an unequal society and to what degree schools impact the social order. A premise in this field is that a fundamental aim of critical education is exposing unequal social, cultural, and economic power relations and engaging in social action that transcends the setting of the classroom and school. Counterhegemonic schools are thus generally characterized by an aspiration to be meaningful beyond the school community and a commitment to social transformation. Purpose/Focus of Study: The study examines a unique bilingual, multicultural school in Israel/Palestine in its struggle to be broadly meaningful and sustainable by opening up enrollment beyond its binational (Jewish-Palestinian) community. In particular, the study analyzes the impact of incorporating external students on the school's counterhegemonic curricula, pedagogy, and dynamics, as well as the implications for the transformative potential of bottom-up democratic education initiatives in the absence of accompanying policy change more generally. Research Design: The findings draw on data collected in a broader qualitative case study on multicultural, bilingual schools educating for democracy and social justice in different national, political, and cultural contexts. Data were collected and analyzed from semistructured open-ended individual interviews with school staff, parents, and founders; field observations; and document analysis. Findings: The primary finding of this research is the paradox of being impacted while making an impact: The school's attempt to infiltrate the hegemony and expand and sustain its social impact led to the infiltration of external goals, interests, and power relations into its counterhegemonic agenda, curricula and pedagogy, and governance. This in turn undermined transformativity and transcultural border-crossing potential at the school and triggered a neoliberal process of commodification. Yet it also emerged that students still succeed in crossing national and religious identity-borders and in overcoming hegemonic perspectives of their essentialized identities. Conclusions: Many obstacles stand between a counterhegemonic school and being socially meaningful, including sociohistorical and political factors. No less important, however, are the broader structural aspects to creating a space in which transformative schools can succeed. Although bottom-up attempts may push hegemonic forms to incorporate certain aspects of their vision, they cannot have meaningful and widespread impact if unaccompanied by broad support and action at the policy level and if they do not become organic parts of a larger transformative agenda.